Outcomes of single‐ vs double‐cuff artificial urinary sphincter insertion in low‐ and high‐risk profile male patients with severe stress urinary incontinence. (22nd March 2016) - Ahyai, Sascha A.; Ludwig, Tim A.; Dahlem, Roland; Soave, Armin; Rosenbaum, Clemens; Chun, Felix K‐H.; Fisch, Margit; Schmid, Marianne; Kluth, Luis A.
Abstract : Objectives: To evaluate continence and complication rates of bulbar single‐cuff (SC) and distal bulbar double‐cuff (DC) insertion in male patients with severe stress urinary incontinence (SUI) according to whether the men were considered low or high risk for unfavourable artificial urinary sphincter (AUS) outcomes. Patients and Methods: In all, 180 male patients who underwent AUS implantation between 2009 and 2013 were followed according to institutional standards. Patients with previous pelvic radiation therapy, open bulbar urethral or UI surgery ('high risk') underwent distal bulbar DC (123 patients) insertion, all others ('low risk') had proximal bulbar SC (57) insertion. Primary and secondary endpoints consisted of continence and complication rates. Kaplan–Meier analysis determined explantation‐free survival, and Cox regression models assessed risk factors for persistent UI and explantation. Results: The median follow‐up was 24 months. Whereas there was no significant difference in pad usage/objective continence after SC vs DC insertion, superior rates of subjective/social continence and less persistent UI were reported by the patients with DC devices (all P ≤ 0.02). Overall, device explantation (erosion, infection or mechanical failure) occurred in 12.8% of patients. While early (<6 weeks) complication rates compared with SC patients were similar ( P > 0.05), DC patients had a 5.7‐fold higher risk of device explantation during late follow‐up ( P = 0.02) and significantly shorter explantation‐free survival (log‐rank, P = 0.003). Conclusions: Distal bulbar DC insertion in patients with a 'high‐risk' profile (previous pelvic radiation, urethral surgery) leads to similar objective continence, but higher explantation rates when compared with patients considered 'low risk' with proximal bulbar SCs. Randomised controlled trials comparing both devices will be needed to determine whether the higher explanations rates are attributable to the DC device or to underlying risk factors.